American education, meritocratic ideology, and the legitimation of inequality : the community college and the problem of American exceptionalism - Brint, Steven [Verfasser]; Karabel, Jerome [Verfasser] (My University, 1989)
"This article examines American education in comparative perspective, suggesting that the distinctive structure of the school system is both an embodiment and a source of the felt fluidity of class boundaries in the United States. Several characteristic features of the American educational system are identified: the avoidance of early selection, the lack of sharp segmentation between different types of institutions, relative freedom of movement both among and within institutions, openness to new fields of study, high levels of enrollment, and the provision of opportunities for educational mobility well into adulthood. The two-year public community college, it argues, is an essential expression of these patterns which, through its very accessibility, reinforces the American ideology that it is never too late for individudal talent to reveal itself - and to be rewarded. The article concludes with a discussion of the effects of the nation's distinctive school system on American culture und politics, suggesting that the perceived "classlessness' of American society may in part be a product of its seemingly open and democratic structure of education." (author's abstract) ((en)) In einem Vergleich mit Europa wird das Bildungssystem der USA im Zusammenhang mit der geringen Bedeutung von Grenzen zwischen sozialen Klassen, mit vertikaler Mobilität und Chancengleichheit analysiert. Das amerikanische Bildungssystem ist gekennzeichnet durch den Verzicht auf frühe Selektion, durch den Mangel an deutlichen Schranken zwischen Bildungseinrichtungen unterschiedlichen Typs, durch relativ grosse Bewegungsfreiheit sowohl zwischen wie innerhalb der Bildungseinrichtungen, Aufgeschlossenheit für neue Studiengänge und berufsorientierte Curricula, hohe Studentenzahlen und die Vermittlung von Chancen für Bildungsmobilität bis weit ins Erwachsenenalter hinein. Die amerikanische Ideologie, dass es für individuelle Talententfaltung und entsprechende Belohnung nie zu spät sei, illustriert das 'Community College' mit seinem offenen Zugang und seiner Verwertbarkeit. Abschliessend werden Zusammenhänge des amerikanischen Schulsystems mit Aspekten des kulturellen und politischen Hintergrunds erörtert. (IAB)
Das amerikanische Bildungssystem, meritokratische Ideologie und die Legitimation der Ungleichheit.
Keywords: T 4.5 Soziologie; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; S 1.1 Allgemeinbildende Schule; G 1.2.2.2 Soziale Sicherungssysteme; G 1.3.3.3 Mobilität; S 1 Stufen der Berufsbildung; G 2.3 Wandel von Arbeit & Wirtschaft; Bildungschancengleichheit; Chancengleichheit; Schulwesen; Soziale Klasse; Vertikale Mobilität; Soziale Mobilität; Bildungssystem; Klassengesellschaft; Bildungsertrag